Checklist of beetles in the subgenus Copris (Paracopris) Balthasar from Asia with description of a new species, and redescription of Copris (Paracopris) punctulatus Wiedemann (Coleoptera: Scarabaeidae: Scarabaeinae) - Bui, van Bac; Ziegler, Thomas; Bonkowski, Michael (Zootaxa, 2019)
We present the first checklist of Asian beetles of the subgenus Copris (Paracopris) Balthasar, 1939 including new data on the distribution. In addition, Copris (Paracopris) javanensis Bui, Ziegler & Bonkowski, new species from Java (Indonesia) is described and Copris (Paracopris) punctulatus Wiedemann, 1823 is redescribed based on specimens deposited in the Muséum National d’Histoire Naturelle (Paris, France), including detailed illustrations of both sexes and male genitalia. At the same time, a neotype is designated for C. (P.) punctulatus as the type specimen was lost.